Food Safety Evaluation of Rice Husk Charcoal Production as a Natural Food Colorant: A Good Manufacturing Practices (GMP) Study in Purworejo Regency - Wahjuningsih, Sri Budi; Siqhny, Zulhaq Dahri; Azkia, Mita Nurul; Utari, Febiani Dwi (Journal of Agritechnology and Food Processing, 2025)
Rice husk charcoal powder is traditionally used in Indonesia as a natural black food colorant, offering potential as an eco-friendly additive while valorizing agricultural waste. However, ensuring its food safety is critical for broader market adoption. This study evaluated the safety and production quality of rice husk charcoal powder produced by a small-to-medium enterprise (SME) in Purworejo Regency, Central Java, using a combined Good Manufacturing Practices (GMP) assessment and laboratory testing. GMP compliance was assessed against 18 parameters outlined in the Indonesian Ministry of Industry Regulation No. 75/M-IND/PER/7/2010, scored on a 0–60 scale. Laboratory analyses measured heavy metal content, moisture, ash, pH, and Salmonella contamination. The facility scored 480/1,080 points (44.44%), classified as Category C (Adequate), with key deficiencies in process monitoring, product labeling, documentation, and recall procedures. Major deviations were linked to open-air carbonization and uncovered cooling, while minor deviations included partial personal protective equipment (PPE) use and semi-open storage. Laboratory results confirmed compliance with safety standards, with Pb <0.04 ppm (≤1.0 ppm limit) and negative Salmonella detection. However, moisture content (18.86%) exceeded typical thresholds for dry powdered additives, correlating with suboptimal storage and drying practices. The findings indicate that while the product meets basic food safety requirements, targeted infrastructural upgrades, improved moisture control, formalized SOPs, and enhanced worker training are essential to elevate GMP compliance and support domestic and export market readiness for natural food colorants.